Sustainability of external imbalances: The case of Malaysia - Lau, Evan; Baharumshah, Ahmad Zubaidi (World Scientific, 2003)
The understanding of the sustainable external imbalances over the 1961-2001 for Malaysia is presented in this paper. The empirical results clearly show that inflows and outflows share a common stochastic trend prior to the 1997 Asian crisis while in the post-crisis period the current account surpluses are on an unsustainable path. Our findings highlight the important role of imports (mainly intermediate inputs) in exports. For an economy that depends on export promotion for its growth process, imports are important in restoring external imbalances to its sustainable steady state path. As illustrated by the recent crisis, the large depreciation of the ringgit contributed to a decline in imports and for an economy that is highly dependent on imported capital, this means an economic slowdown.